Factors associated with Pneumocystis colonization and circulating genotypes in chronic obstructive pulmonary disease patients with acute exacerbation or at stable state and their homes. (3rd November 2021) - Gantois, Nausicaa; Lesaffre, Aymerick; Durand-Joly, Isabelle; Bautin, Nathalie; Le Rouzic, Olivier; Nseir, Saad; Reboux, Gabriel; Scherer, Emeline; Aliouat, El Moukhtar; Fry, Stéphanie; Gosset, Philippe; Fréalle, Emilie
Abstract: Pneumocystis jirovecii colonization is frequent during chronic obstructive pulmonary disease (COPD) and patients constitute potential contributors to its interhuman circulation. However, the existence of an environmental reservoir cannot be excluded. We assessed the prevalence and factors associated with Pneumocystis colonization during COPD, and studied circulation between patients and their domestic environment. Pneumocystis molecular detection and mtLSU genotyping were performed in oro-pharyngeal washes (OPW) sampled in 58 patients with COPD acute exacerbation, and in indoor dust, sampled in patients' homes using electrostatic dust collectors (EDCs). Lung and systemic inflammation was assessed. Pneumocystis carriage was evaluated in 28 patients after 18 months at stable state. Pneumocystis was detected in 11/58 OPWs during exacerbation (19.0%). Colonized patients presented a significantly lower body mass index, and higher serum IL-17 and CD62P. One patient presented positive detection of typable isolates in both OPW and EDC, with both isolates harboring mtLSU genotype 3. Pneumocystis genotype 1 was further detected in EDCs from three non-colonized patients and one colonized patient with non-typable isolate. Genotypes 1 and 2 were predominant in clinical isolates (both 42%), with genotype 3 representing 16% of isolates. Pneumocystis was detected in 3/28 patients at stable state (10.7%). These data suggest that Pneumocystis colonization could be facilitated by a lower BMI and be related to acute alteration of lung function during COPD exacerbation. It also suggests Th17 pathway and platelet activation could be involved in the anti- Pneumocystis response during colonization. Last, Pneumocystis detection in EDCs supports its potential persistence in indoor dust. Lay Summary: Chronic obstructive pulmonary disease patients tend to be more frequently colonized by Pneumocystis during exacerbation (19.0%) than at stable state (10.7%). Factors associated with colonization include lower BMI, higher IL-17, and CD62P. Pneumocystis detection in patients' dwellings suggests potential persistence in indoor dust.